How Extremist Movements Delegitimise Religious Moderation Campaigns: a Case of Hizbut Tahrir Indonesia (2018-2022) - Alvian, Rizky Alif (Perspectives on terrorism, 2023)
This article examines how extremist movements respond to the mainstreaming of religiously moderate teachings as strategies for preventing violent extremism (PVE). Focusing on the case of Hizbut Tahrir Indonesia (2018-2022), this article argues that extremist movements react to religious moderation campaigns by operating a malign influence operation intended to delegitimise the projects. To do so, the movements try to undermine the trust of the Muslim audience in democratic values that underpin the idea of religious moderation, as well as authorities and community members who appear supportive of the campaigns. While the substance of the campaigns is labelled as incompatible with the ‘true’ Islamic teachings, the extremists also portray supportive authorities and community members as having malicious interests against Islam. Once distrust of the campaigns and their messengers is sown, the extremists then urge the Muslim audience to return to the ‘true’ Islam, resisting authorities, and contest the influence of community members supportive of the religious moderation campaigns. This study, therefore, sheds light on how extremist movements perceive and counter the promotion of religious moderation as an instrument of PVE.